Transformational Leadership and Work Engagement: The Moderating Role of Intrinsic Motivation - Barbara Grah; Vlado Dimovski; Marko Perić; Simon Colnar; Sandra Penger (Economic and Business Review, 2024)
We examine the moderating role of intrinsic motivation in the relationship between transformational leadership and work engagement. In a sample of 168 tourism and hospitality employees in the quantitative section, Study 1, we found that the highest level of work engagement is identified when the level of intrinsic motivation is highest. Intrinsically motivated employees then exhibit engaged behaviors at work. In Study 2, we opted for a descriptive design to better understand the findings of Study 1, using interviews with three experts and a three-phase coding analysis. We found that increasing intrinsic motivation further promotes engaged work behavior. This article provides insight into the benefit of intrinsic motivation on work engagement and offers practical guidance to tourism and hospitality stakeholders by demonstrating how intrinsic motivation functions as an essential management concept in adapting after the coronavirus pandemic.